GROWTH OF ANGSANA (Pterocarpus indicus Willd) MYCORRHIZAE 23 MONTHS AGE IN POST GOLD MINING - Husna Husna; Asrianti Arif; Faisal Danu Tuheteru; Akbar Akbar; Albasri Albasri; Wiwin Rahmawati Nurdin (Journal of Tropical Mycorrhiza, 2022)
Arbuscular Mycorrhizal Fungi (AMF) technology can increase the success of revegetation on post-mining land. In addition to the input of AMF technology, the selection of plant species is very important for the success of post-mining land reclamation. This study aimed to determine the effectiveness of AMF on the viability and growth of the 23-month-old mycorrhizal Angsana (Pterocarpus indicus Willd.) in the post-Bombana gold mining area, Southeast Sulawesi. This research was conducted in the post-gold mining area of ​​PT. Panca Logam Makmur, North Rarowatu District, Bombana Regency and the Laboratory Unit of the Forestry Department, Faculty of Forestry and Environmental Sciences Halu Oleo University, Kendari for 8 months. The research design used a Randomized Block Design which was divided into nine treatments; control (A0), Claroideoglomus etunicatum (A1), Septoglomus constrictum A2), Acaulospora delicata (A3), Glomus claroideum (A4), Glomus coronatum (A5), Ambiospora appendicula (A6), Mixed AMF I (A7); (A1+A2+A6) and Mixed AMF II (A8); (A1+A3+A4+A5). The total number of plants used was 27 plants. The results showed that the application of arbuscular mycorrhizal fungi was effective in increasing the growth of P. indicus plants in post-gold mining areas. The treatment of G. coronatum, G. claroideum, A. appendiculate, and C. etunicatum significantly increased the growth of 23 months old P. indicus plant on post-gold mining land compared to control and other treatments. G. coronatum and G. Claroideum have the potential to be developed as mycorrhizal biofertilizers.